Analisis Penentuan Persediaan Singkong Sebagai Bahan Baku Tape Singkong Pada Agroindustri Peuyeum Abas Sawargi, Kecamatan Cimenyan, Kabupaten Bandung - Kuswarini Kusno; Annisaa Punjul Rahayu; Eti Suminartika; Anne Charina (Paspalum: Jurnal Ilmiah Pertanian, 2018)
Cassava as the third staple food for the people of Indonesia after rice and corn, is the raw material for making ‘tape singkong”. Agroindustry Peuyeum Abas Sawargi located in District Cimenyan, Bandung Regency buy cassava almost every day to make “tape singkong”. It's not economical and inefficient; therefore good cassava inventory management is required. The purpose of this research was to determine the amount of economical cassava inventory and to know when to re-order the cassava so that the total cost of inventory to be a minimum, as well as comparing the actual cost of inventory to those based on economical cassava inventory. The research design was qualitative with case study technique. The collected data consists of primary data year 2017 and secondary data which were analyzed descriptively and quantitatively by Economic Order Quantity (EOQ) and Reorder Point (ROP) methods.. The results showed that the amount of cassava inventory that must be available was 3,264 kg with the frequency of ordering 61 times a year, while the re-ordering of cassava must be carried out when the remaining cassava stock of 2,240 kg. As a result, total inventory costs decreased by almost 48% within a year.  Thus, the production process becomes more efficient and in the long run the agroindustry can be expected to be more competitive.